1996
DOI: 10.1046/j.1365-2826.1996.05207.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tuberoinfundibular Dopaminergic Neural Activity During Suckling: Involvement of μ and κ Opiate Receptor Subtypes

Abstract: Previous studies have shown that mu (mu) and kappa (kappa) opioid antagonists inhibit suckling-induced prolactin release. Prolactin responses elicited by pup suckling or opioid administration are mediated, at least in part, by suppression of dopamine (DA) release from tuberoinfundibular dopaminergic (TIDA) neurons in the hypothalamus. We examined the effects of the mu opiate receptor antagonist, beta-funaltrexamine (beta-FNA), and the kappa opiate receptor antagonist, nor-binaltorphimine (nor-BNI) on the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 33 publications
4
25
2
Order By: Relevance
“…Therefore, pertussis toxin-induced inactivation of G i /o -proteins coupled to the -opioid receptors in the hypothalamus could produce a disinhibition of dopaminergic neurons and result in increased release of dopamine. Increased dopamine levels in the anterior pituitary gland inhibit the secretion of prolactin, regardless of the presence of other stimuli that increase its secretion (Pilotte and Porter, 1981;Callahan et al, 1996). This explanation is consistent with the observation that pertussis toxin treatment reduced basal prolactin levels.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, pertussis toxin-induced inactivation of G i /o -proteins coupled to the -opioid receptors in the hypothalamus could produce a disinhibition of dopaminergic neurons and result in increased release of dopamine. Increased dopamine levels in the anterior pituitary gland inhibit the secretion of prolactin, regardless of the presence of other stimuli that increase its secretion (Pilotte and Porter, 1981;Callahan et al, 1996). This explanation is consistent with the observation that pertussis toxin treatment reduced basal prolactin levels.…”
Section: Discussionsupporting
confidence: 84%
“…For example, receptors that are coupled to pertussis toxin-sensitive G i -proteins, such as -opioid receptors (Parolaro et al, 1990;Chan et al, 1995), mediate a tonic inhibition of the activity of tuberoinfundibular dopamine neurons in the hypothalamus (Callahan et al, 1996). Therefore, pertussis toxin-induced inactivation of G i /o -proteins coupled to the -opioid receptors in the hypothalamus could produce a disinhibition of dopaminergic neurons and result in increased release of dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous observations indicate that EOP and opiate agonists suppress the activity of TIDA neurons by activation of µ- and/or ĸ-receptors [49, 50, 51, 52], thereby increasing the prolactin secretion [53, 54]. In the present study, we did not find an inverse correlation between prolactin levels and DOPAC/DA ratio after DAMGO or β-END administration.…”
Section: Discussioncontrasting
confidence: 63%
“…Similar results have been obtained using specific opiate receptor antagonists. Administration of either the µ or ĸ receptor antagonists inhibited prolactin release during suckling [19], but only the µ site seemed to mediate inhibition of hypothalamic dopaminergic neural activity [30]. Furthermore, β-endorphin stimulated prolactin secretion in both virgin and postpartum female rats and this response was antagonized by specific µ 1 [21], µ, δ and ĸ [22]sites, indicating the involvement of multiple receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…This response was abolished by antagonizing the µ 1 [21], µ, δ or ĸ sites [22]indicating that β-endorphin activates a pathway involving multiple receptor subtypes. In lactating female rats, antagonism of either the µ or ĸ receptor site inhibited prolactin release during suckling [19], but only the µ site seemed to mediate inhibition of hypothalamic dopaminergic neural activity [30]. Arbogast and Voogt [1]recently reported that opioidergic input was essential for normal lactation due to the effects on the TIDA neurons.…”
Section: Introductionmentioning
confidence: 99%